Schizophrenia and epigenetics: a comprehensive bibliometric analysis - Abd. Rahim, Nour El Huda; Abdull Jalil, Mohd Asyraf; A.Talib, Norlelawati; Mat Rasid, Siti Norain; Wan Salleh, Wan Muhamad Salahudin; Azman, Norainin Sofiya; Mohamed Bakrim, Norbaiyah (Springer Nature, 2023)
Background and objective(s): Numerous studies have explored the association between epigenetics and schizophrenia, yielding various findings and reports. Thus, we conducted a bibliometric analysis of the studies that have investigated this association to provide an overview of the evolution of research on this topic and to determine the current status and areas for advancement in this field. Methods: We applied several methodologies, such as keyword co-occurrence and co-authorship analysis, to the SCOPUS database to analyze the most significant authors, institutions, and countries and the most cited publications. Several analytic tools were employed, namely Bibliomagika 2.2 and Bibliomagika 1.5 Split for frequency analysis, VOSviewer for data visualization, and Biblioshiny packages from R software to perform the bibliometric analysis. Results: A total of 397 publications were retrieved, and most were published in 2013, revealing an increasing trend over the past decade. The most productive contributors based on the number of published documents were Alessandro Guidotti (24 publications), University of Illinois at Chicago (21 publications), the United State of America (159 publications), and the Journal of Schizophrenia Research (22 publications). The top keywords were schizophrenia (250 occurrences), DNA methylation (174 occurrences) and epigenetics (121 occurrences). Conclusions: The findings shed light on the research trends, country contributions, influential authors, and most active journals on the topic. This information can help researchers to identify gaps and future directions in the field and can provide a platform for progressing knowledge in this field.